Synaptic dysfunction reflected in CSF: serial CSF sampling reveals trajectories of potential synaptic biomarkers in early AD stages. (20th December 2022) - Duits, Flora H.; Nilsson, Johanna; Teunissen, Charlotte E.; Zetterberg, Henrik; Blennow, Kaj; Scheltens, Philip; van der Flier, Wiesje M.; Brinkmalm, Ann
Abstract: Background: Synaptic dysfunction plays an important role in Alzheimer's disease (AD) and cognitive decline. Using serial CSF sampling we investigated longitudinal trajectories of synaptic proteins, including SYT1, SNAP25, neurogranin, synucleins, neuronal pentraxins (NPTX) and three 14‐3‐3 proteins, in AD. Methods: We included 150 subjects with subjective cognitive decline (SCD; 62±7 years), mild cognitive impairment (MCI; 66±8 years) or AD dementia (64±7 years) from the Amsterdam dementia cohort, based on availability of CSF at two time points and clinical follow‐up of more than one year (median[interquartile range] 3.3[2.1‐5.1] years). Synaptic proteins were analyzed using two different mass spectrometry‐based assays. We used linear mixed models to assess whether baseline protein levels and slopes over time differed between groups (first analysis), and to assess associations of protein levels with cognitive function at baseline and decline over time, measured by repeated MMSE (second analysis). We first compared groups according to baseline diagnosis. Secondly, non‐demented subjects were compared based on CSF AD profile (i.e. abnormal Ab42 and tau levels; 60 AD‐ and 40 AD+ subjects). All protein levels were transformed to Z‐scores for comparison of effect sizes and were evaluated in separate models. Results: At baseline levels of SNAP25, neurogranin, beta‐synuclein and 14‐3‐3 proteins were higher in AD dementia than in SCD and MCI (figure 1), and in non‐demented AD+ versus AD‐ subjects. NPTX‐2 levels were lower in AD compared with SCD. Over time SYT1, NPTX‐1, NPTX‐2 and NPTX‐receptor decreased in AD dementia patients (st.B between ‐0.10 and ‐0.15; figure 2A), while 14‐3‐3 zeta/delta increased in MCI subjects (st.B[SE] 0.08[0.03]). Similar changes were seen in non‐demented AD+ subjects (Figure 2B). In SCD subjects lower baseline levels of NPTX‐2 were associated with lower baseline MMSE. In SCD and MCI subjects higher levels of SNAP25, Ng, synucleins and 14‐3‐3 proteins were associated with faster cognitive decline. Conclusion: CSF levels of SYT1 and NPTX decreased over time in subjects with early symptomatic AD, while higher baseline levels of other synaptic proteins were associated with future disease progression. This dissociation may reflect complex synaptic changes in early disease stages and may have added value in a prognostic model for AD.